Faithful disobedience: writings on church and state from a Chinese house church movement - Wang, Yi (IVP Academic, 2022)
"In this important body of theology, key writings from the Chinese house church movement have been compiled, translated, and made accessible to English speakers. This unique resource will be valuable to practical and political theologians and anyone interested in international relations, political philosophy, history, and intercultural studies"--